Measuring Violence Against Children: A COSMIN Systematic Review of the Psychometric and Administrative Properties of Adult Retrospective Self-report Instruments on Child Abuse and Neglect - Steele, B.; Neelakantan, L.; Jochim, J.; Davies, L.M.; Boyes, Mark; Franchino-Olsen, H.; Dunne, M.; Meinck, F. (SAGE PUBLICATIONS INC, 2023)
Valid, meaningful, and reliable adult retrospective measures of violence against children (VAC) are essential for establishing the prevalence, risk factors, and long-term effects of VAC. We aim to summarize the available evidence on the psychometric properties of adult retrospective VAC measures and to provide evidence-based recommendations for appropriate measure selection. We searched six electronic databases and gray literature for studies that report on the development, content validity, or psychometric properties of adult retrospective child abuse and neglect measures for this review (PROSPERO: CRD4201706). We used the 2018 Consensus-based Standards for the selection of health Measurement Instruments (COSMIN) criteria to evaluate each included study and measure. We assessed if measures included questions on frequency or severity, the perpetrator, or the location of the violence, and noted the administrative practicalities for each instrument such as length, readability, available translations, and cost to access. We identified 288 studies and 77 measures. The quality of evidence ranged from “low” to “high,” depending on the measure and the psychometric properties assessed. The measures with the most robust evidence available across multiple contexts are the: ACE and ACE-IQ; FBQ and FBQ-U; CTQ and CTQ-SF; and ICAST-R. This review shows the strengths and weaknesses of retrospective VAC measures. The substantial evidence presented in this review can be used by researchers to make psychometrically sound decisions for measurement selection which should be supported by extensive piloting and adaptation to the respective local context.